Control interno y su incidencia en la cartera de crédito de la cooperativa de ahorro y crédito Juan Pio De Mora, sucursal Quevedo, período 2012 - Almeida Huayamabe, Paola Rebeca (2015)
This fact-finding project has like end to investigate the theme: “Internal control and your incidence in Crédito's Wallet of the Credit Union and Crédito Juan Pio De Mora, subsidiary Quevedo, period 2012, as a mere formality an utilities company was selected with this work, which offers loans to citizenship in general among themselves: Consumption, microcréditos, little boxes, advances to employees the objectives of this work are: Analyzing the Credit Union's incidence of the Internal Control in the wallet of credit and Crédito Juan Pio of Mora, subsidiary Quevedo, period 2012, evaluating the fulfillment of the standards and credit policies, checking the fulfillment of the negotiations of collection of payment that are permitted to recover the wallet defeated of the associates, examining the increment or decrease that maintained the wallet of credit in relation to the previous period 2011-2012, the fact-finding methodology that was used were deductive, inductive the fact that they are the most opportune as to internal control considered itself he receives treatment. As to techniques, to turn to the interview, since it is the method more directly to get information by the speaker's part became necessary. It was checked in the evaluation of the Questionnaire of Internal Control to the adviser of credit that, the inherent risk belongs to the 25 % and in like manner exists a confidence 75 % found in the measurement of risk, the same that has an effect on the Cartera of company Crédito which you affect the financial performance for of the same, factor. Culminating this research work, with the respective findings and presented recommendations, which will make a contribution of mode adapted to the Credit Union and Mora's Crédito Juan Pio, subsidiary Quevedo.